(untitled) (Revista Lusófona de Educação, 2026)
This study aimed to analyze how the disciplinary field of Physical Education is valued by Basic Education teachers, seeking to assess the knowledge that teachers possess regarding the contents of Physical Education, perceive how they integrate them into their pedagogical practices, identify the obstacles that teachers face in teaching Physical Education, and verify whether Curricular Enrichment Activities (Physical and Sports Activities) have implications on the (de)valorization of Physical Education. A semi-structured individual interview approach was adopted, organized around a set of 16 questions conducted with 10 Basic Education teachers from 2 school clusters in Viseu’s district. Teachers acknowledge Physical Education’s importance for children holistic development; however, from a teaching perspective, they do not value it, citing as main causes the lack of material and spatial resources, insufficient personal preparation, and a perceived lack of security in their training; teachers advocate for adjuvated models by a specialized teacher in the field. Despite the concern expressed by teachers, as they consider Physical Education extremely important for children’s holistic development and essential for practice in the school context, they do not teach it significantly, ultimately leading to its devaluation in practice.